Non-Ideal Smoothing Transformer as Effective Differential Mode Filter - Dürbaum, Thomas; Stahl, Jürgen; Junghaenel, Rene; Albach, Manfred (IEEE Energy Conversion Congress & Exposition, September 2012, 2012)
Reducing differential mode (dm) noise of switching converters in an effective way is an open issue. Here, a thorough investigation of the filtering technique with integrated magnetics, taking non-ideal effects into account is done. This means that parasitic components and component variations due to tolerances are considered, and the obtainable attenuation is calculated. Furthermore, this paper gives an analysis of the optimized coupling factor as well as the distribution of the capacitance between the two capacitors involved. The whole analysis is done in the frequency domain. Therefore, a proper model is given. In order to show the relevance of this work a practical validation is presented. © 2012 IEEE.
UnivIS-Import:2015-03-09:Pub.2012.tech.IE.lselek.nonide